Associations between both legacy and alternative per- and polyfluoroalkyl substances and glucose-homeostasis: The Isomers of C8 health project in China. (January 2022) - Zhang, Yun-Ting; Zeeshan, Mohammed; Su, Fan; Qian, Zheng-Min; Dee Geiger, Sarah; Edward McMillin, Stephen; Wang, Zhi-Bin; Dong, Peng-Xin; Ou, Yan-Qiu; Xiong, Shi-Min; Shen, Xu-Bo; Zhou, Pei-En; et al.
Graphical abstract: Highlights: We provided more evidence on associations between legacy PFASs and PFAS alternatives and glucose-homeostasis. We explored the joint associations of legacy PFASs and PFAS alternatives. 6:2 Cl-PFESA contributed the most in the joint associations. Sex-specific associations were observed. Abstract: Background: Epidemiological studies on the associations of legacy per- and polyfluoroalkyl substances (PFASs) and glucose homeostasis remain discordant. Understanding of PFAS alternatives is limited, and few studies have reported joint associations of PFASs and PFAS alternatives. Objectives: To investigate associations of novel PFAS alternatives (chlorinated perfluoroalkyl ether sulfonic acids, Cl-PFESAs and perfluorobutanoic acid, PFBA) and two legacy PFASs (Perfluorooctanoic acid, PFOA and perfluorooctane sulfonate, PFOS) with glucose-homeostasis markers and explore joint associations of 13 legacy and alternative PFASs with the selected outcomes. Methods: We used cross-sectional data of 1, 038 adults from the Isomers of C8 Health Project in China. Associations of PFASs and PFAS alternatives with glucose-homeostasis were explored in single-pollutant models using generalized linear models with natural cubic splines for PFASs. Bayesian Kernel Machine Regression (BKMR) models were applied to assess joint associations of exposures and outcomes. Sex-specific analyses were also conducted to evaluate effect modification. Results: After adjusting for confounders, both legacy (PFOA, PFOS) and alternative (Cl-PFESAs and PFBA) PFASs were positively associated with glucose-homeostasis markers in single-pollutant models. For example, in the total study population, estimated changes with 95% confidence intervals (CI) of fasting glucose at the 95th percentile of 6:2Cl-PFESA and PFOS against the thresholds were 0.90 (95% CI: 0.59, 1.21) and 0.44 (95% CI: 0.26, 0.62). Positive joint associations were found in BKMR models with 6:2Cl-PFESA contributing most. Sex-specific associations existed in both single- and multi-pollutant models. Conclusions: Legacy and alternative PFASs were positively associated with glucose-homeostasis markers. 6:2Cl-PFESA was the primary contributor. Sex-specific associations were also identified. These results indicate that joint associations and effect modification should be considered in risk assessment. However, further studies are recommended to strengthen our findings and to elucidate the mechanisms of action of legacy and alternative PFASs.